Hospitalization rates for pneumococcal disease in Brazil, 2004 - 2006 - Hillegonda Maria Dutilh Novaes; Ana Marli Christovam Sartori; Patricia Coelho de Soárez (Universidade de São Paulo, 2011)
OBJECTIVE: To estimate hospitalization rates for pneumococcal disease based on the Brazilian Hospital Information System (SIH). METHODS: Descriptive study based on the Hospital Information System of Brazilian National Health System data from January 2004 to December 2006: number of hospitalizations and deaths for pneumococcal meningitis, pneumococcal sepsis, pneumococcal pneumonia and Streptococcus pneumoniae as the cause of diseases reported in Brazil. Data from the 2003 Brazilian National Household Survey were used to estimate events in the private sector. Pneumococcal meningitis cases and deaths reported to the Notifiable Diseases Information System during the study period were also analyzed. RESULTS: Pneumococcal disease accounted for 34,217 hospitalizations in the Brazilian National Health System (0.1% of all hospitalizations in the public sector). Pneumococcal pneumonia accounted for 64.8% of these hospitalizations. The age distribution of the estimated hospitalization rates for pneumococcal disease showed a "U"-shape curve with the highest rates seen in children under one (110 to 136.9 per 100,000 children annually). The highest hospital case-fatality rates were seen among the elderly, and for sepsis and meningitis. CONCLUSIONS: PD is a major public health problem in Brazil. The analysis based on the SIH can provide an important input to pneumococcal disease surveillance and the impact assessment of immunization programs.